2013
DOI: 10.1167/iovs.13-11595
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Streptozotocin-Induced Diabetic Rat Retinal Function and Ocular Blood Flow to Acute Intraocular Pressure Challenge

Abstract: STZ-induced diabetes increased functional susceptibility during acute IOP challenge. This functional vulnerability is associated with a reduced capacity for diabetic eyes to upregulate eNos expression and to autoregulate blood flow in response to stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 59 publications
0
17
0
1
Order By: Relevance
“…These functional abnormalities are mainly neuronal in origin; and neuronal cell apoptosis can be seen as early as one month after induction of diabetes [34,35]. Abnormal ERG responses appear before vascular lesions begin to appear; streptozotocin-induced diabetic rats present delayed ERG responses within one month of induction of diabetes [36], while retinal capillary cell apoptosis and histopathology are not observed till the duration is extended to at least 6 months [32]. Similarly, alterations in multifocal ERG are considered to predict the onset and progression of retinopathy in diabetic patients [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…These functional abnormalities are mainly neuronal in origin; and neuronal cell apoptosis can be seen as early as one month after induction of diabetes [34,35]. Abnormal ERG responses appear before vascular lesions begin to appear; streptozotocin-induced diabetic rats present delayed ERG responses within one month of induction of diabetes [36], while retinal capillary cell apoptosis and histopathology are not observed till the duration is extended to at least 6 months [32]. Similarly, alterations in multifocal ERG are considered to predict the onset and progression of retinopathy in diabetic patients [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia has multiple effects that can potentially impact not only AION onset [11][12][13] and second eye involvement, 14,15 but also visual outcome once optic nerve ischemia occurs. Other than the well-known effects of hyperglycemia on blood vessels, [31][32][33][34][35] there is also evidence that diabetes increases cellular inflammation, [36][37][38][39] which can be directly attributed to hyperglycemia. 40 In hyperglycemia, there is known upregulation of levels of retinal VEGF, which is secreted by Müller cells in vivo and in vitro, [41][42][43] which can prime the hyperglycemic retinal milieu to develop greater swelling and more prominent inflammation in ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Three weeks after diabetes induction, which is considered sufficient time to induce chronic diabetes, 31 we induced experimental AION using photochemical thrombosis 23,25,26 following injection of rose bengal (1.25 mM in phosphatebuffered saline, 5 lL/g body weight) in tail vein using transpupillary laser light with a frequency doubled Nd:YAG laser (Pascal; OptiMedica, Santa Clara, CA, USA) at 400-lm spot diameter (50 mW power, 1 second duration, 15 spots). To ensure consistency of studies, the same person performed AION induction in all experiments, and one eye in each mouse had AION induction, whereas the contralateral (fellow) eye served as control.…”
Section: Experimental Aion and Experimental Groupsmentioning
confidence: 99%
“…Ocular blood flow was measured using laser Doppler flowmetry in a manner similar to previous studies (Kiel and van Heuven ; Wong et al. ). To determine the origin of the LDF signal, a pilot study (He et al.…”
Section: Methodsmentioning
confidence: 99%
“…Ocular blood flow was measured using laser Doppler flowmetry in a manner similar to previous studies (Kiel and van Heuven 1995;Wong et al 2013). To determine the origin of the LDF signal, a pilot study (He et al 2012, online supplement) showed that hyperoxemia induced by pure oxygen breathing suppressed the LDF signal by 18%.…”
Section: Experimental Protocolmentioning
confidence: 99%